Pengaruh literasi ekonomi dan lingkungan sosial terhadap perilaku pembelian impulsif pada mahasiswa - Novi Pujiastuti; Reza Reza; Ratna Fitri Astuti (Jurnal Riset Pendidikan Ekonomi, 2022)
The role of economic literacy and the social environment is important in causing impulsive buying behavior in student purchases. This study aims to determine how the influence of economic literacy and social environment on students' impulsive buying behavior. The data was collected by distributing questionnaires to 132 students and interviewing 15 students to find out responses to the state of economic literacy, social environment, and students' impulsive buying behavior. Based on the results of the study, it is found that there is a partial and significant influence between economic literacy on student impulse buying behavior, a partial influence between social environment on impulsive buying behavior, a simultaneous influence between economic literacy and social environment on impulsive buying behavior. With the application of the knowledge of economic literacy that students have, and not following the culture or habits that exist in the surrounding environment in purchasing so that students' impulsive buying behavior does not occur.